Problematic soils: in search for solution - Kim Huat, Bujang (Universiti Putra Malaysia Press, 2010)

(untitled)
Soils are considered to include all naturally occurring loose or soft deposits overlying the solid bedrock. They are formed from the disintegration and decomposition of rocks and also by decomposition of organic materials. Compared with rocks, soils are softer in terms of strength and more compressible, thus giving more problems to engineering works as compared with rocks. However are soils really a problem, or is it the theory? Perhaps the latter is more valid. The soils found in Malaysia can generally be termed as tropical soils. They range from residual soils which are normally soils formed by in-situ weathering of parent rocks to soft clays and organic soils, including peat. Soft soils generally have low shear strength and high compressibility. As such, problems like large settlements, flooding and damage to infrastructure due to soil subsidence, foundation failure due to lateral movement of soil, etc, are common. Residual soils on the other hand are generally considered to be better in terms of engineering properties, compared with soft soils, but by virtue of their existence on sloping ground, landslides become a major concern. Over 400 landslides have been reported in the country over the last two decades (more than 30 were major landslides), involving both cut and natural slopes with a total loss of more than 200 lives and billions of Ringgit in damage to property.In meeting the above mentioned challenges, some research works have been done at University Putra Malaysia. These include proper analysis and design of piles against lateral loading; fundamental understanding on the properties and behavior of soft soils, both soft clays and peat; methods to improve/stabilize the soils; slope assessment system for landslide prediction, bio-engineering techniques to stabilize slopes; and use of waste materials as an economical solution to repair slopes. These works are briefly described in this inaugural lecture booklet